The Employment of the Roma - Evidence from Hungary - Gabor Kertesi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2004)
The paper is based on data of individual work histories of the 1993/94 representative Roma survey in Hungary. First the disappearance of full employment of Roma in the 1984-1994 period is documented by the use of a quasi cross-sectional macro model and the patterns of employment characteristics of the nineties are described. Then the erosion of employment is traced from individual histories controlling the effects of gender, age and schooling. Finally, particular aspects of low employment of Roma are accounted for, focusing on the role of low schooling, regional backwardness, and labour market discrimination.
Keywords: J15; J7; R23; 330; Economics of minorities and races; Discrimination; Regional inequalities; Transition